Electronic Structures of Graphene/MoS2 Heterostructure: Effects of Stacking Orientation, Element Substitution, and Interlayer Distance - Dian Putri Hastuti; Kenji Nawa; Kohji Nakamura (Universitas Gadjah Mada, 2023)
Effects of stacking orientation, element substitution, and interlayer distance on electronic structures of graphene/MoS2 heterostructures were investigated using first-principles calculations. The results predicted that the stacking orientation does not take a crucial role in changing the electronic structures in contrast to element substitution, which converts the system from semiconductor to metallic. A bandgap opening originating in a Dirac band of graphene is found to be governed by the interface distance between graphene and MoS2 layers.